hubungan pola makan dan aktivitas fisik terhadap kadar gula darah pasien DM - Sugi, Chut Atzel Guslia Putri; maryuni, sri; sari, nova nurwinda (Universitas Aufa Royhan, 2024)
Diabetes is a chronic metabolic disease characterized by increased blood sugar levels (hyperglycemia).Diabetes is caused by diet, unhealthy habits, stress, and lack of exercise. The aim of this research is to determine the relationship between diet and physical activity on blood sugar levels in DM patients at the Beringin Raya Community Health Center, Bandar Lampung City in 2024.the type of research used is quantitative research using a cross-sectional survey design and overall sampling techniques.The samples used in this research were all DM patients who were in the work area of ​​the Beringin Raya Community Health Center during the period January to June 2024, totaling 61 people and my sample who were there were 61 people.Data collection used questionnaires and glucose tests, and the data analysis technique used was the chi-square test. The results of the research show that the statistical test of the relationship between diet and blood sugar produces a value of (0.000), and the statistical test of the relationship between physical activity and blood sugar produces a value of (0.037).